Plasma Protein of Obese White Rats Treated with of Glucomannan Porang Tubers and Moringa Extract - Ikhsani, Sabila Dina; Setyaningsih, Endang (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Living things have a fluid that flows throughout the body, namely blood. Blood contains blood cells as well as a fluid called blood plasma. Plasma is a mixture of blood with anticoagulants. Plasma protein levels are influenced by body weight, age, growth, etc. Weight in particular, is closely related to obesity. This study aimed to determine the blood plasma protein levels of obese white rats given a mixture of glucomannan porang tubers and moringa leaf extract. This research method uses true experimental which is prepared with a Complete Randomized Design (RAL) in the form of posttest Only Control Design. The data obtained were analyzed using One Way ANOVA SPSS version 20 followed by the Kruskal willis test. The results of this study showed plasma protein levels between groups, namely (P1) 1358.6; (P2) 1356.6; (P3)1356.6; (P4)1353.6; (P5)1356; (P6)1359; (P7)1357.6; (P8)1360 from the above results it can be concluded that the blood plasma protein levels of obese white rats treated with a mixture of glucomannan and Moringa leaf extract were the highest at 1360 g / dL and the lowest plasma protein levels of 1353.6 g / dL.